Dielectric Permittivity in Copper Leaching: A Review - Marcos Andreu; Robert Zwick; Moe Momayez (Sensors)
The leaching process for copper extraction has garnered significant attention due to its critical role in meeting the rising demand for copper, driven by global trends towards decarbonization and electrification. The accurate measurement of variables is essential for process control, prompting the development of advanced sensor technologies. This paper reviews the applications of dielectric permittivity measurements in the mining industry, focusing on their potential to enhance the monitoring and optimization of copper leaching processes. It evaluates the suitability of permittivity-based sensors, analyzing their advantages and limitations, and discusses the implications for process control and economic optimization. The study highlights the integration of permittivity measurements into existing monitoring systems, aiming to improve efficiency, reduce environmental impact, and increase ore recovery rates. This comprehensive review provides insights into the current state of permittivity measurement technologies and their future prospects in the context of copper leaching.